Cybervictimization, self-esteem, and social relationships among German secondary school students. (2nd October 2018) - Lohbeck, Annette; Petermann, Franz
ABSTRACT: By differentiating between five specific forms of cybervictimization (denigration, betrayal, social exclusion, cyberstalking, happy slapping), the present study examined the multifaceted structure of cybervictimization and specific relationships o these five forms of cybervictimization with students' self-esteem and social relationships. Moreover, mediating effects of self-esteem were explored. Factor analyses supported the five-factor structure. Self-esteem and social relationships were negatively related to almost all five forms of cybervictimization. However, hierarchical regression analysis showed that only student–student relationships were negatively predictive of social exclusion, while only teacher–student relationships were negatively predictive of denigration, betrayal, and cyberstalking. Further, self-esteem appeared to be a negative predictor and mediator of denigration and social exclusion. Girls experienced more betrayal than boys. Older students reported lower social exclusion but more cyberstalking than younger students.